The User Experience with Visual Impairment and Web Evaluation Processes: The Case of the Observatory of Accessible and Inclusive Technologies (OTAI) Costa Rica 2019 - Rodríguez Vega, Wilmer (2020)
Web accessibility assessments are a growing labor and technology market in Costa Rica. In this scenario, the participation of people with disabilities in the evaluation processes becomes mainly relevant. The Observatory of Accessible Technologies (OTAI) of the Technological Institute of Costa Rica makes contributions in this regard by incorporating assessors with visual disabilities as part of the permanent work team. The objective of this work is to express the user experience of an evaluator with visual impairment who experiences his experience when expressing his needs under general compliance criteria that may impact more than one possible end user. The contribution of this is that, within the emergence of the importance of digital accessibility in Costa Rica and Latin America; and the growing market of web evaluations in the country, the possibility of having evaluators with disabilities who verify the criteria in light of their needs will open future employment doors in a scenario that is still in early stages in the region and our country.